Use the FOIL (first, outside, inside, last) to expand the terms in the brackets.
(w - 7)(w + 4)
first: w × w = w²
outside: w × 4 = 4w
inside: -7 × w = -7w
last: -7 × 4 = -28
Now you add all the terms together to get:
w² + 4w - 7w - 28
This simplifies to give you:
w² - 3w - 28
Hope that helps! :)
Answer:
up 10
Step-by-step explanation:
The function would change from
C(x) = 0.3x + 40
to
C(x) = 0.3x + 50
The change is only to the y-intercept, so the graph of the function will move up 10.
Answer:
ndjwjddjskwsjdb
Step-by-step explanation:
nfnjwkwjdjdiwsjndnskiwis
Answer:
Hello! i don't see the underlined digit
(-3,4)
Is
The
Correct answer